Artificial intelligence in work environments: its impact on the efficiency and effectiveness of human resource management and productivity enhancement - Debbah, Hocine; Boughazi, Naouel (The International tax journal, 2025)
This study explores the role of artificial intelligence (AI) in enhancing human resource management. It examines how AI contributes to core HR processes: recruitment, performance appraisal, training, and planning. We applied a descriptive Analytical approach to study the connection between AI and HR activation. Our key finding shows that AI constitutes a fundamental shift in HR management. AI automates routine tasks, streamlines, procedures and delivers customized solutions. This leads to more efficient recruitment, training, performance management, and compensation. The study concludes with recommendations for businesses to adopt AI in HR, aiming to save time, reduce costs, and enhance excellence.